Assessment of the Epidemiological Effectiveness of the Temporary Transfer of Schoolchildren to Distance Learning during the Spread of COVID‑19 by the Example of the Saratov Region - A. A. Zimirova; V. E. Kuklev; V. A. Safronov; E. V. Kuklev; I. N. Vyatkin (Проблемы особо опасных инфекций, 2023)
Temporary closure of schools is an effective anti-epidemic measure during periods of rising incidence of acute respiratory viral infections and influenza, which is confirmed by the results of a large number of scientific works. In particular, the effectiveness of this measure consists in reducing the incidence among students. In the context of the spread of COVID‑19 in the Russian Federation, like in many other countries, the temporary transfer of schoolchildren to distance learning has also been repeatedly introduced; however, it remains unclear whether the measure under consideration is effective in relation to the new coronavirus infection.The aim of the study was to assess the epidemiological effectiveness of the temporary transfer of students to distance learning during the spread of COVID‑19 in the Saratov Region.Materials and methods. The analysis was carried out on the basis of statistical data of the Rospotrebnadzor Administration in the Saratov Region on the incidence of COVID‑19 for the period of 2020–2022, as well as materials from published scientific papers.Results and discussion. Analysis of the data on the school closure in 2020 has revealed a decrease in the incidence among schoolchildren (–42.9 %) and an increase in the incidence among people aged 65 years and older (+7.2 %); in 2021, there was a decrease in the incidence among schoolchildren (–15.6 %) and an increase in the indicator value as regards the elderly (+17.8 %); in 2022, another school closure led to an increase in the incidence of COVID‑19 among schoolchildren (+7.8 %) and people over 65 years old (+44.2 %). Based on the results obtained, one can conclude that the measure under consideration is inexpedient due to the fact that the most vulnerable category of the population (persons aged 65 years and older) is actively involved in the epidemic process, which in turn leads to a significant deterioration of the epidemic situation.